The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.2337/db15-0568
|View full text |Cite
|
Sign up to set email alerts
|

Methylglyoxal-Induced Endothelial Cell Loss and Inflammation Contribute to the Development of Diabetic Cardiomyopathy

Abstract: The mechanisms for the development of diabetic cardiomyopathy remain largely unknown. Methylglyoxal (MG) can accumulate and promote inflammation and vascular damage in diabetes. We examined if overexpression of the MG-metabolizing enzyme glyoxalase 1 (GLO1) in macrophages and the vasculature could reduce MG-induced inflammation and prevent ventricular dysfunction in diabetes. Hyperglycemia increased circulating inflammatory markers in wild-type (WT) but not in GLO1-overexpressing mice. Endothelial cell number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 50 publications
(59 reference statements)
7
70
1
Order By: Relevance
“…The early stages of diabetic cardiomyopathy are commonly characterised by LV diastolic dysfunction and ventricular hypertrophy, and in later stages by LV systolic dysfunction progressing to decompensated heart failure [3,5]. Consistent with previous studies [14], our data confirm the presence of LV diastolic dysfunction at 16 weeks of age in Akita mice. Evaluation of both Doppler flow and tissue Doppler echocardiography revealed that 16 weeks of hyperglycaemia conferred a reduction in e′/a′ ratio and E/A ratio, and a prolongation of deceleration time (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…The early stages of diabetic cardiomyopathy are commonly characterised by LV diastolic dysfunction and ventricular hypertrophy, and in later stages by LV systolic dysfunction progressing to decompensated heart failure [3,5]. Consistent with previous studies [14], our data confirm the presence of LV diastolic dysfunction at 16 weeks of age in Akita mice. Evaluation of both Doppler flow and tissue Doppler echocardiography revealed that 16 weeks of hyperglycaemia conferred a reduction in e′/a′ ratio and E/A ratio, and a prolongation of deceleration time (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Results are expressed as mean ± SE of mean (n = 3). # shows a significant difference (<0.05) when compared to control, *shows a significant difference (<0.05) when compared to MG vascular dysfunction among other complications, such as aging and hypertension (Nigro et al, 2017;Vulesevic et al, 2016). El-Bassossy et al (2016) even went on to argue that MG is responsible for an amplified contractile response similar to that observed in diabetes.…”
Section: Discussionmentioning
confidence: 97%
“…Such vascular dysfunction is mostly characterized by an amplified vascular contraction which consequently hinders complete vasodilation (Bahia et al, ). The use of MG to study such vascular complications is justified by recent studies claiming that MG accumulation in the body is associated with vascular dysfunction among other complications, such as aging and hypertension (Nigro et al, ; Vulesevic et al, ). El‐Bassossy et al () even went on to argue that MG is responsible for an amplified contractile response similar to that observed in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Deoxyactein decreases the production of IL-1β in MG-exposed RIN-m5F cells. MG promotes the formation of pro-inflam- matory cytokines in various cell types (26)(27)(28). Thus, we also investigated whether deoxyactein modulates the production of IL-1β in MG-exposed cells (Fig.…”
Section: Effects Of Deoxyactein On the Viability Of Rin-m5f Cellsmentioning
confidence: 99%